# Graphing Lie Derivative

I am relatively new to differential geometry. I am studying it from Fecko Textbook on differential geometry. As soon as he introduces the concept of lie derivative,he asks to do exercise 4.2.2 in picture. The question is,how do I apply ##\phi^*## to given function ##\psi## . I know that ##\phi^*## transport tensor fields against direction of flow. But how it does,I don't know.

Can anyone help me?

#### Attachments

• 31.4 KB Views: 288

Related Differential Geometry News on Phys.org
Orodruin
Staff Emeritus
Homework Helper
Gold Member
But how it does,I don't know.

Consider case (i) first. An integral curve of V is Φ(t, x) = t + x because dΦ/dt = 1 and Φ(0, x) = x. What happens to a point x? Its shifted to t + x. What happens to a function ψ(x)?

Consider case (i) first. An integral curve of V is Φ(t, x) = t + x because dΦ/dt = 1 and Φ(0, x) = x. What happens to a point x? Its shifted to t + x. What happens to a function ψ(x)?
It becomes ##\phi= e^{-(x+t)^2}##. Is this the answer? Can you give procedure to calculate lie derivative like that for case 2?

Last edited:
It becomes ##\phi= e^{-(x+t)^2}##. Is this the answer?
yes, and the problem asks you to draw the graph of ##f##. You draw the curve as a function of ##t## for a fixed ##x##, which is the initial point. (Don't name the function ##\phi## to avoid confusion with the curve, which the problem already calls ##\phi##.)
Can you give procedure to calculate lie derivative like that for case 2?
The Lie Derivative is something else. It's when you take the limit $$\lim_{t \longrightarrow 0} \frac{ \phi^*_t f - f}{t}.$$ What you need to do:

1 - Find the integral curves for the given vector field.
2 - Displace the curve by an infinitesimal amount and take the limit as I gave above.

For case (i) this is ##\phi(\epsilon, x) \equiv x' = x + \epsilon V##, but ##V = 1##, then ##x' = x + \epsilon##. So ##f(x') \approx f(x) + \epsilon df/dx## and ##\mathcal L_V f = df / dx##. In our case, ##f (x) = \exp (-x^2)##. So ##\mathcal L_V \exp (-x^2) = -2x \exp (-x^2)##.

Can you try yourself case (ii)?

Abhishek11235